Potret Implementasi Kurikulum Merdeka Dalam Pembelajaran Bahasa Indonesia Di MTSN 03 Subang - Firial Fauziyah Diba; Hindun Hindun (Populer: Jurnal Penelitian Mahasiswa, 2024)
The aim of this research is to find out how this curriculum is implemented, in Indonesian language lessons in class VII MTs Negeri 3 Subang, how the independent curriculum is implemented. This research was conducted qualitatively and data was collected through observation, interviews and questionnaires. The research results show that the Project Based Learning (PBL) approach, formative evaluation and literacy improvement for students, are all used to adopt the independent curriculum. The implementation of this curriculum has resulted in increased student independence and the development of soft skills. Overall, the Merdeka Curriculum at MTs Negeri 3 Subang supports student independence, facilitates critical learning, and develops Pancasila character. The obstacles faced require further attention to increase the effectiveness of curriculum implementation, although there are obstacles related to the availability of books and teacher understanding. The effectiveness of the curriculum is assessed through student self-evaluation and teacher observation. Limited resources and teachers' understanding of the curriculum are some of the obstacles. This research provides insight into the difficulties and opportunities of an independent curriculum to improve the quality of education at the secondary level.